Nitrogen Fluxes in an Agro-Livestock System under Land Use Change: A Temporal Analysis in an Environmental Protection Unit - Angélica Cristina Rhoden; João Garibaldi Almeida Viana; Vicente Celestino Pires Silveira; Thierry Christophe Bonaudo; Gilberto Vilmar Kozloski (Agriculture, 2023)
In recent decades, significant changes have driven the advancement of agricultural production systems in Brazil. The objective of this study is to analyze the efficiency and transformation of the agricultural production system in the Ibirapuitã Environmental Preservation Area (EPA) through nitrogen input and output flows. Methodologically, the approach is considered mixed, consisting of a case study and based on quantitative and qualitative techniques. Flowcharts and indicators were elaborated to evaluate nitrogen flows over time. The results were confirmed through semi-structured interviews. The results indicated that production based on economic efficiency is one of the main factors transforming the livestock system. The transformation of the production system into livestock did not reduce nitrogen flows. Productive and economic indicators reaffirm the transformation and volatility of livestock systems under economic and political contexts, even in an environmental protection unit.